Neurophysiological and clinical biomarkers of secondary progressive multiple sclerosis: A cross-sectional study - Tartaglia, Matteo; Canevelli, Marco; Malimpensa, Leonardo; Belvisi, Daniele; Baione, Viola; Ferrazzano, Gina; Leodori, Giorgio; Berardelli, Alfredo; Conte, Antonella (Frontiers in Neurology, 2023)
Timely diagnosis of secondary progressive multiple sclerosis (SPMS) represents a clinical challenge. The Frailty Index, a quantitative frailty measure, and the Neurophysiological Index, a combined measure of sensorimotor cortex inhibitory mechanism parameters, have recently emerged as promising tools to support SPMS diagnosis. The aim of this study was to explore the possible relationship between these two indices in MS. MS participants underwent a clinical evaluation, Frailty Index administration, and neurophysiological assessment. Frailty and Neurophysiological Index scores were found to be higher in SPMS and correlated with each other, thus suggesting that they may capture similar SPMS-related pathophysiological mechanisms.